An advanced climate resilience indicator framework for airports: A UK case study. (December 2021) - Poo, Mark Ching-Pong; Yang, Zaili; Dimitriu, Delia; Qu, Zhuohua
Highlights: Elaborate all the indicators influencing airport climate resilience. Develop a climate resilience evaluation method using evidential reasoning. Use big data to quantify the airport climate resilience. Conduct an empirical study to analyse the climate resilience of the UK airports. Abstract: Due to increased extreme weather events, climate adaptation has become an essential issue to be addressed by all transport infrastructures, including airports. This paper aims to develop a Climate Resilience Indicator (CRI) framework for assessing airport climate resilience, which for the first time, considers: climate exposure, vulnerability and adaptive capacity simultaneously and advances the development of climate risk analysis of airports to a point where their adaptation and resilience can be quantified under uncertainty in data. Climate-related data was collected from multiple sources to evaluate an airport's performance against each indicator. An evidential reasoning (ER) approach is used to evaluate each airport by integrating all the indicators to derive its final CRI score. The findings provide valuable insights into how urgently an airport needs to deal with climate change and reveal information to help with resource allocation for different airports nationally through proactive adaptation planning.